PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, KEBIJAKAN DIVIDEN, TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Faridah, Nur; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
By implementing the function of financial management, then the optimization of firm value can be achieved. A single financial decision which has been determined will have an influence to other financial decisions. Financial decision which has been determined will have an impact to the firm value. This research is meant to test the influence of investment decision, funding decision, dividend policy, and the interest rates to the firm value. The research samples are 30 manufacturing companies which are listed in Indonesia Stock Exchange from 2012 until 2014 and these companies have been selected by using purposive sampling. The data source of this research has been done by using multiple linear regressions analysis with the application instrument is SPSS (Statistical Product and Service Solutions). The result of this research shows that: (1) investment decision has positive influence to the firm value, (2) the financial decision does not have any influence to the firm value, (3) dividend policy has negative influence to the firm value, and (4) interest rates does not have any influence to the firm value.Keywords: Investment Decision, Funding Decision, Dividend Policy, Interest Rates, and Firm Value.